Enfermedad de Letterer Siwe Abt - Borbolla Vacher, Liane; Guernica de Roux, Antonio; Geigel González, Juan José; De Armas Curbelo, Lidia; González Falcón, María; Dueñas Gómez, Enzo (Revista Cubana de Pediatría, 2023)
Presentación de caso.